2013
DOI: 10.1177/194008291300600503
|View full text |Cite
|
Sign up to set email alerts
|

Nutmeg-Vertebrate Interactions in the Asia-Pacific Region: Importance of Frugivores for Seed Dispersal in Myristicaceae

Abstract: In tropical forests, large frugivores are assumed to be important seed dispersers for many large-seeded trees such as the Myristicaceae, a widespread and common family. However, not all frugivores are effective seed dispersers, and understanding which frugivores are effective is vital for conservation biology. Here, we summarize the available data on fruit characteristics and frugivores for a large number of Myristicaceae species in the Asia-Pacific region and suggest future directions for evaluating the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 112 publications
1
5
0
Order By: Relevance
“…Generally speaking, the lack of direct observations and data on actual seed removal events leaves uncertain the respective role of frugivore species, limiting the robustness of our conclusions. Despite these shortcomings, the studied large‐seeded tree species appears to have a highly specialized dispersal strategy, as confirmed by other studies on Myristicaceae species in Asia (Kitamura & Poonswad ), Central America (Howe & Vande Kerckhove , ), and South America (Holbrook & Loiselle , Queenborough et al . , Ratiarison & Forget , Boissier et al .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Generally speaking, the lack of direct observations and data on actual seed removal events leaves uncertain the respective role of frugivore species, limiting the robustness of our conclusions. Despite these shortcomings, the studied large‐seeded tree species appears to have a highly specialized dispersal strategy, as confirmed by other studies on Myristicaceae species in Asia (Kitamura & Poonswad ), Central America (Howe & Vande Kerckhove , ), and South America (Holbrook & Loiselle , Queenborough et al . , Ratiarison & Forget , Boissier et al .…”
Section: Discussionsupporting
confidence: 60%
“…Generally speaking, the lack of direct observations and data on actual seed removal events leaves uncertain the respective role of frugivore species, limiting the robustness of our conclusions. Despite these shortcomings, the studied large-seeded tree species appears to have a highly specialized dispersal strategy, as confirmed by other studies on Myristicaceae species in Asia (Kitamura & Poonswad 2013), Central America (Howe & Vande Kerckhove 1980, 1981, and South America (Holbrook & Loiselle 2009, Queenborough et al 2013, Ratiarison & Forget 2013, Boissier et al 2014. Plants with a restricted seed disperser assemblage are known to be particularly sensitive to human disturbances (Howe et al 1985, Cordeiro & Howe 2003, Holbrook & Loiselle 2009, Uriarte et al 2011, Ratiarison & Forget 2013, especially when they have large seeds that only larger vertebrates can ingest and disseminate (Vanthomme et al 2010, Markl et al 2012.…”
Section: Discussionmentioning
confidence: 69%
“…The distribution area of H. tetratepala is mainly affected by the tropical monsoon climate, in which the average annual temperature is 20~25 • C and the average annual rainfall is 1500~3500 m [49]. Research has shown that the seeds of this species are mainly dispersed by frugivorous birds, mammals, some reptiles and gravity dispersal [50,51]. During a field survey in 2018, the species was found to be disappearing due to the expansion of banana and rubber cultivation and tourism development.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate frugivores are often presumed to carry seeds long distances (e.g., Jordano et al, 2007 ;Lees and Peres, 2009 ;Lenz et al, 2011 ), but the shape of the dispersal kernel can vary with the disperser and ecological context. Long-distance seed dispersal of hundreds to thousands of meters by birds and bats has been documented many times, especially for canopy trees (e.g., Hardesty et al, 2006 ;Seidler and Plotkin, 2006 ;Kays et al, 2011 ;Kitamura et al, 2011 ;Kitamura and Poonswad, 2013 ;Seltzer et al, 2013 ). But birds of closed-canopy understories are relatively sedentary and loath to cross water and habitat barriers ( Diamond et al, 1976 ;Moore et al, 2008 ).…”
mentioning
confidence: 99%